2012
DOI: 10.2466/04.07.it.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3D Virtual Simulators in the Introductory Wind Energy Course: A Tool for Teaching Engineering Concepts

Abstract: Effects of 3D virtual simulators in the introductory wind energy course: a tool for teaching engineering concepts. Innovative Teaching, 2, 7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
7
0
2
Order By: Relevance
“…Do et al. () considered that one of the advantages of VR is to make an abstract concept concrete. Osberg () and Bhagat, Liou, and Chang () proved that VR could increase the motivation of users and cause them to focus more on learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Do et al. () considered that one of the advantages of VR is to make an abstract concept concrete. Osberg () and Bhagat, Liou, and Chang () proved that VR could increase the motivation of users and cause them to focus more on learning.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the rapid development of computer hardware and software, as well as cost reduction in hardware equipment, has raised the popularity in the use of three-dimensional (3D) virtual reality (VR) with computer simulations as a training method. Do et al (2013) considered that one of the advantages of VR is to make an abstract concept concrete. Osberg (1995) and Bhagat, Liou, and Chang (2016) proved that VR could increase the motivation of users and cause them to focus more on learning.…”
Section: Introductionmentioning
confidence: 99%
“…Em virtude disso, surge a exigência fundamental de melhorar a formação de novas gerações de profissionais para a indústria eólica. Essa etapa requer um cuidado e a necessidade de uma eficaz transferência de conceitos aprendidos em sala de aula para prática, que, dada a complexidade da tarefa, pode ser uma barreira que dificulta a performance do aprendizado, e consequentemente, a formação do profissional [3]. As metodologias de ensino como ferramentas de simulação e uso de realidade virtual mostram-se adequadas para mitigar as limitações de ensino em sala de aula.…”
Section: Introductionunclassified
“…Em se tratando do contexto do campo da engenharia, posteriormente, novos engenheiros, serão diplomados com uma formação mais sólida e poderão desempenhar melhor sua principal função que é oferecer soluções práticas e inovadoras para problemas em sua área profissional [4], [5], [6] e [7]. Propostas de aprimoramento das técnicas de educação no contexto da energia eólica são apresentadas na forma de simuladores virtuais 3D em diferentes temáticas que envolvem estudo dos componentes internos e externos do aerogerador, forças aerodinâmicas atuantes, efeito esteira, monitoramento remoto de sistemas de controle, além de posicionamento de aerogeradores em um parque eólico, com uso de realidade virtual e aumentada [3], [8], [9] e [10].…”
Section: Introductionunclassified
“…Based on the research result, it is found that students have motivation in learning by using technology. [28] research on Effects of 3D virtual simulators in the introductory wind energy course: a tool for teaching engineering concepts, This research provides innovative solutions in effective learning and is able to improve the postsecondary education by developing virtual simulators that can be integrated with the school curriculum. Critical acquisition of educating and training a professional generation in industry, the development and implementation of virtual simulators in the accompanying curriculum will foster national reform in the United States, Thus meeting the needs of the wind energy industry movement and addressing the broader educational issues in a number of disciplines.…”
mentioning
confidence: 99%